APOLOGY STRATEGIES USED BY EFL LEARNERS OF UNIVERSITAS RIAU - Nurzikralaila Mukti; Indah Tri Purwanti; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study was conducted to analyzing EFL Learners’ strategy in apologizing. This was a descriptive qualitative study using a qualitative approach combine with descriptive statistics. The participants of this study were 32 EFL Learners that currently study in their second academic year in English Department of Universitas Riau. They were selected using cluster random sampling technique. The data was collected online using a DCT (Discourse Completion Task) containing 8 situation which required participants to write down their responses for each situation. The result revealed that participants are capable to use a wide variety of apology strategies. Moreover, they have tendency to use more than one strategy in one situation.Key Words: Apology strategy, DCT, .